Good kids from bad neighborhoods : successful development in social context - Elliott, Delbert S.; Menard, Scott W.; Rankin, Bruce H. (Bruce Howard); Elliott, Amanda; Huizinga, David; Wilson, William J., 1935- (Cambridge University Press, 2006)
This is a study of successful youth development in poor, disadvantaged neighborhoods in Denver and Chicago - a study of how children living in the worst neighborhoods develop or fail to develop the values, competencies and commitments that lead to a productive, healthy responsible adult life.
Keywords: Youth with social disabilities -- United States.; Community organization -- United States.; Children -- United States -- Social conditions.; Neighborhoods -- United States.; Jeunes socialement défavorisés -- États-Unis.; Organisation communautaire -- États-Unis.; Enfants -- États-Unis -- Conditions sociales.; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare.; POLITICAL SCIENCE -- Public Policy -- Social Security.; Children -- Social conditions; Community organization; Neighborhoods; Youth with social disabilities; United States; Electronic books.